Pergolakan Keagamaan dan Pemberontakan Raden Trunojoyo Terhadap Mataram Tahun 1674-1680 M - An’nisa Imania; Lailatul Huda; Wasid (Qurthuba: The Journal of History and Islamic Civilization, 2022)
Abstract: The Trunojoyo rebellion (1674-1680) aimed to overthrow Amangkurat I from his throne. This study seeks to answer the formulation of the problem, namely; (1) How was the beginning of the Raden Trunojoyo Rebellion in 1674-1680?, (2) How was the involvement of the Dutch in the Raden Trunojoyo rebellion in 1674-1680?, (3) How was the anti-Dutch attitude and religious spirit carried out by Raden Trunojoyo's troops during the rebellion take place?. The research uses historical research methods with historical narrative approaches and socio-political movement approaches, as well as Challenge and Response theory by Arnold Joseph Toynbee. The results of the research are; (1) The beginning of the rebellion was caused by Amangkurat I often collaborating with the VOC which led to influencing the Mataram government system, he often carried out unjust actions and was not as capable as Sultan Agung and brought suffering to the people. (2) The involvement of the VOC in the rebellion was since Amangkurat I asked for help from the VOC and then participated in the battle until the Mataram and VOC troops succeeded in defeating Raden Trunojoyo's troops, (3) The anti-Dutch attitude and religious spirit manifested itself in the spirit of fighting against the VOC in the name of religion. Islam and the spirit of Islam that was continuously ignited by religious leaders, namely Panembahan Kadjoran and PanembahanGiri. Keywords: Dutch Hate, Trunojoyo Rebellion, Religious Spirit